Perspectives on social pacts in Spain: Social dialogue and the social partners - Sylvia Rohlfer (Management Revue, 2012)
The return of social pacts in the context of the current economic crisis, as seen in southern European countries, invites the revival of the discussion about the development of social dialogue practice in its specific context. Based on a longitudinal analysis we examine the agenda of Spanish tripartite social pacts. We do this by assessing their priorities and the actors' strategies for their involvement in social dialogue by taking the overall political, legal and social context into account. The results are then used to discuss the future implications for Spanish social partners. Challenges regarding the future role of the social partners in collective bargaining, their political exchange and their dependence on political allies are observed.
Keywords: J50; J51; J53; 650; social pacts; social dialogue practice; social partners; Spain